Ecologically oriented analysis of the reasons holding back litter processing - Zazykina Lyubov; Roiter Liya; Gusev Valentin (E3S Web of Conferences, 2023)
The article deals with the problems of disposal and processing of litter, substantiates the relevance of their solution in the industry. Various points of view on the conceptual apparatus of litter are considered and the author's vision is given, the essence of which lies in the allocation of litter to by-products. Based on this, it is proposed to consider this type of product as a market potential for expanding its product portfolio. The reasons hindering the disposal and processing of litter are studied, their systematization is clearly given with the rationale for each of the presented block of reasons and possible management decisions. The analysis of the problems and causes hindering the process of disposal and processing of litter indicates the need to continue research on the designated issue from the standpoint of expanding the market potential of this type of by-product and developing existing management solutions and finding new approaches to filling the relevant market niches. This will contribute to the development of the market potential of litter processing products and increase the added value of the own capital of economic entities in the industry.